DESIGN AND CONSTRUCT AN OPEN DIE FORGING MACHINE WITH A 1.5 HP ELECTRIC MOTOR AND 5 KG HAMMER - Armila Armila; M. Iqbal Darussalam; Rudi Kurniawan Arief (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2024)
This project outlines the design and construction of an open forging machine equipped with a 1.5 HP electric motor and a 5 kg hammer for use in the Material Technology Laboratory. The primary objective was to create a versatile and controlled environment for forging and shaping materials. The project began with the conceptualization and design phase, where the layout and components of the machine were planned. Materials were carefully selected for durability and performance. Construction was meticulously carried out with an emphasis on safety.The machine underwent rigorous testing to ensure it met the laboratory's specific requirements, and adjustments were made for optimal performance. Fine-tuning was performed to calibrate the machine, addressing temperature control, speed, and pressure settings. The completed open forging machine promises to enhance research capabilities in material technology, facilitating experiments in material science and research. This project represents a significant step in advancing the laboratory's capabilities and marks the beginning of a new phase in material technology research and experimentation.Keywords: Forging Machine, Electric Motor, Hammer, Material,Laboratory Equipment